Attribution of wrongful actions by the Pro-Russian rebels in the Eastern Ukraine to Russia - Pakula, Artemijs (Riga Graduate School of Law, 2023)
Since the beginning of the Russian invasion in Ukraine, the numerous and various violations of international law by the army of Russian Federation have come to light. However, Russian presence and impact on the Eastern Ukraine are not limited to the war that begun in February 2022. On the contrary, its agents and intelligence have been active in subverting and undermining the Ukrainian sovereignty in these territories since at least 2014 through proxies in the form of the so-called “Donetsk and Luhansk People’s Republics”. This paper focuses on the existing rules as set out in the Articles on State Responsibility for Internationally Wrongful Acts regarding the attribution of private actors to States. Through an analysis of the landmark Nicaragua, Tadič, and Bosnian Genocide cases, and the two control tests arising therefrom, standards of attribution of such acts are derived. These extracts are then applied to the works of two courts, the District Court of the Hague, and the European Court of Human Rights, on the matter, to determine, if the actions of said “republics” can be attributed to Russia under international law. The findings indicate that the current rules of attribution, despite their seeming strictness and harshness, nevertheless create a framework sufficient for the attribution of acts of violation of Ukrainian sovereignty to Russia.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; State responsibility; State attribution; Ukraine; Russia